The subversive power of laughter: Plato and Aristotle on humour - Daly, E (2021)
Plato explicitly theorises about laughter in three dialogues: Republic (388a-389a, 605c-607a); Philebus (47e-50b); and Laws (816d-817a, 935a-936a). Although it is not possible to construct an overarching Platonic “theory” of laughter, this thesis argues, based on Platonic moral psychology and epistemology, that Plato is preoccupied with the subversive potential of laughter in the soul and state (subversive laughter) while also allowing for a socially and ethically positive form of laughter (playful laughter). Aristotle is generally seen as taking a more positive view of humour and laughter than Plato: he includes εὐτραπελία (wittiness) as a virtue in the Nicomachean Ethics (1127b34-1128b9). This thesis will show how Aristotle’s philosophising on laughter emerges, converges, and diverges from Plato’s “theories” of laughter, arguing that laughter for Aristotle can be either subversive or playful, and that the latter always has the potential to turn into the former. Finally, this thesis will show how the influence of Plato and Aristotle on modern humour theory (the Superiority Theory and the Incongruity Theory) should not be underestimated and so sheds further light on why we laugh and whether it is possible for laughter ever to be free from subversive potential.